Hypertension and Cognitive Impairment: A Review of Mechanisms and Key Concepts - Canavan, Michelle; O'Donnell, Martin J. (Frontiers in Neurology, 2022)
Cognitive impairment, and dementia, are major contributors to global burden of death and disability, with projected increases in prevalence in all regions of the world, but most marked increases in low and middle-income countries. Hypertension is a risk factor for both Vascular Cognitive Impairment and Alzheimer's disease, the two most common causes of dementia, collectively accounting for 85% of cases. Key end-organ pathological mechanisms, for which hypertension is proposed to be causative, include acute and covert cerebral ischemia and hemorrhage, accelerated brain atrophy, cerebral microvascular rarefaction and endothelial dysfunction, disruption of blood-brain barrier and neuroinflammation that affects amyloid pathologies. In addition to the direct-effect of hypertension on brain structure and microvasculature, hypertension is a risk factor for other diseases associated with an increased risk of dementia, most notably chronic kidney disease and heart failure. Population-level targets to reduce the incidence of dementia are a public health priority. Meta-analyses of blood pressure lowering trials report a significant reduction in the risk of dementia, but the relative (7–11%) and absolute risk reductions (0.4% over 4 years) are modest. However, given the high lifetime prevalence of both conditions, such relative risk reduction would translate into important population-level reductions in dementia globally with effective screening and control of hypertension. Optimal blood pressure target, especially in older adults with orthostatic hypotension, and antihypertensive agent(s) are uncertain. In this review article, we will detail the observational and interventional evidence linking hypertension with cognitive impairment, summarizing the mechanisms through which hypertension causes cognitive decline.